Long-term follow-up of patients with relapsed/refractory multiple myeloma after BCMA CAR-T-cell therapy - Hao, Yuanyuan; Wang, Zhen; Zhang, Lei; Bai, Yanliang; Yuan, Xiaoli; Yang, Jing; Jiang, Li; Niu, Junwei; Cheng, Wei; Li, Wei; Huang, Zhoufeng; Chen, Yuqing; et al. (Frontiers in Immunology, 2025)
BackgroundB-cell maturation antigen (BCMA)-directed chimeric antigen receptor (CAR) T-cell therapy has demonstrated potent short-term efficacy in patients with relapsed/refractory multiple myeloma (R/R MM); however, long-term clinical data remain limited. Here, we report extended follow-up outcomes from our single-center experience.MethodsBetween August 20, 2018, and December 31, 2021, 11 patients with R/R MM received BCMA-targeted CAR-T-cell therapy at our center. Preconditioning consisted of cyclophosphamide and fludarabine chemotherapy, followed by infusion of 1–5×106 CAR+ T cells/kg. We evaluated overall response rate (ORR), long-term efficacy, safety profiles, and their correlations with clinical/disease characteristics.ResultsThe ORR was 72.7% (8/11), including 6 complete remissions (54.5%) and 2 partial/very good partial remissions. With a median follow-up of 23 months (range: 2–63 months), 75% (6/8) of the responders remained relapse-free, and 4 patients (50%) were alive at the time of data cutoff. The median progression-free survival (PFS) and overall survival (OS) of responders both reached 35 months. In terms of safety, most patients experienced moderate cytokine release syndrome (CRS), with 2 cases of grade 3–4 CRS.ConclusionBCMA CAR-T-cell therapy exhibits favorable safety and efficacy in advanced R/R MM. Long-term follow-up confirmed durable responses in 50% of the advanced R/R MM patients who responded to the treatment (4/8).